Wired for Sound: Review of Patterns in the Mind, by Ray Jackendoff [and] The Language Instinct, by Steven Pinker - Dennett, Daniel C. (Tufts Archival Research Center, 2014)
This article was originally published in the London Review of Books (http://www.lrb.co.uk/). Permission has been granted to reproduce the piece on the Tufts Digital Library. ; Dennett, Daniel C. "Wired for Sound: Review of Patterns in the Mind, by Ray Jackendoff [and] The Language Instinct, by Steven Pinker." The London Review of Books 16, no. 12 (1994): 10-11.